Pelatihan Penyusunan Rencana Anggaran Biaya Talud di Desa Tladan Kecamatan Kawedanan Kabupaten Magetan - Rosyid Kholilur Rohman; Setiyo Daru Cahyono; Seno Aji (Universitas Merdeka Madiun, 2021)
The government promotes rural infrastructure development through Village Fund Allocation (ADD). In the process of planning, development and reporting the village government is given the broadest authority. This authority requires the village government to have the ability to prepare a Budget Plan (RAB) and report on the use of funds. The ability of village communities in preparing Budget Plan for the Talud is still minimal and training is needed to improve their abilities. The results of this training are expected to be beneficial for the people of Tladan Village, Kawedanan District, Magetan regency so that the infrastructure development program in the village will run better and achieved good quality.